Derecruitment volume assessment derived from pressure–impedance curves with electrical impedance tomography in experimental acute lung injury. Issue 8 (August 2020) - Sun, Xiu-Mei; Chen, Guang-Qiang; Wang, Yu-Mei; Zhou, Yi-Min; Chen, Jing-Ran; Cheng, Kun-Ming; Yang, Yan-Lin; Zhang, Lin-lin; Li, Hong-Liang; Zhou, Jian-Xin
Objective: To investigate the accuracy of derecruitment volume (VDER ) assessed by pressure–impedance (P-I) curves derived from electrical impedance tomography (EIT). Methods: Six pigs with acute lung injury received decremental positive end-expiratory pressure (PEEP) from 15 to 0 in steps of 5 cmH2 O. At the end of each PEEP level, the pressure–volume (P-V) curves were plotted using the low constant flow method and release maneuvers to calculate the VDER between the PEEP of setting levels and 0 cmH2 O (VDER-PV ). The VDER derived from P-I curves that were recorded simultaneously using EIT was the difference in impedance at the same pressure multiplied by the ratio of tidal volume and corresponding tidal impedance (VDER-PI ). The regional P-I curves obtained by EIT were used to estimate VDER in the dependent and nondependent lung. Results: The global lung VDER-PV and VDER-PI showed close correlations (r = 0.948, P<0.001); the mean difference was 48 mL with limits of agreement of −133 to 229 mL. Lung derecruitment extended into the whole process of decremental PEEP levels but was unevenly distributed in different lung regions. Conclusions: P-I curves derived from EIT can assess VDER and provide a promising method to estimate regional lung derecruitment at the bedside.